NATRIURESIS, NOT SEIZURES, INDUCED BY CHOLINERGIC STIMULATION OF THE LOCUS-CERULEUS IS AFFECTED BY FOREBRAIN LESIONS AND WATER-DEPRIVATION - Deluca, L. A.; Franci, C. R.; Saad, W. A.; Camargo, LAA; Antunesrodrigues, J. (Elsevier B.V., 1991)
Two groups of rats with electrolytic lesions of the medial and upper septal area (MUL) or, alternatively, of the anteroventral portion of the third ventricle (AV3V) and a third group of sham-operated rats were water loaded and received three carbachol injections into the locus coeruleus according to the following schedule: 1) prelesion, 2) on the second postlesion day and 3) on the seventh postlesion day. Both MUL and AV3V lesions inhibited the carbachol-induced natriuresis on the second postlesion day. Recovery was almost complete after MUL but not after AV3V lesion on the seventh day. Water deprivation also reduced the carbachol-induced natriuresis but passive hydration of AV3V animals did not avoid the impairment induced by the lesion. Transient seizure phenomena such as clonic convulsions, salivation and analgesia subsequent to carbachol injection were not altered by the lesions.
Keywords: LOCUS COERULEUS; SEPTAL AREA; ANTEROVENTRAL 3RD VENTRICLE; SODIUM EXCRETION; NATRIURESIS; WATER DEPRIVATION; WATER INTAKE; CHOLINERGIC STIMULATION; CARBACHOL; SEIZURES